The Passion for Animal in Derrida: Following the Steps of an Outlaw - Asena Ulus (Caliban: French Journal of English Studies)
Derrida contends that the subject defines itself as the supreme ruler by establishing the laws of its home (oikos), thus of its economy (oikos-nomos). This formulation would explain the foundations of the community when it is established around the model of brotherhood. The animal, Derrida argues, since it challenges all the autobiographic projects of the subject, is an outlaw; it transcends the economy. Its arrival stirs a passion in the human being because it narrows down the abysmal distance between them prescribed by this economy. The “Passion for Animal” is a question of ‘passive nudity’ in the face of the singularity of the Other. Therefore, a fair relationship grounded on the singularity of being becomes possible, based not on the principle of metaphysical fraternity but only as a ‘groundless friendship’ evinced by proper noun, mourning, and an insuperable distance. Here lies the promise of the democracy to come.